2002
DOI: 10.1002/1521-4141(200208)32:8<2172::aid-immu2172>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis and molecular modeling of the binding of Staphylococcus aureus enterotoxin C2 to a murine T cell receptor Vβ10 chain

Abstract: We investigated the role of the β chain HV4 region in the binding of a Vβ10 T cell receptor to superantigen S. aureus enterotoxin C2 (SEC2)/MHC class II complexes. Residues 6971 of the Cw3/1.1 TCR Vβ10 chain, derived from an H‐2Kd‐restricted cytotoxic clone, were individually changed to alanine using site‐directed mutagenesis, and mutated TCR β chains were transfected along with the wild‐type TCR α chain into a TCR α–β– T hybridoma. SEC2/MHC recognition was measured by IL‐2 production. Alanine substitutions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…We found an increased frequency of CD4 + T cells in the lymph nodes expressing TCR Vβ10, a receptor that binds S. aureus superantigen enterotoxin C2, in adult ft/ft mice when compared with adult C57BL6 and BALB/c mice, but also when compared with 2‐week‐old ft/ft mice (Fig. a,b) . This indicates an induced expansion of CD4 + T cells expressing TCR Vβ10 in adult ft/ft mice.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…We found an increased frequency of CD4 + T cells in the lymph nodes expressing TCR Vβ10, a receptor that binds S. aureus superantigen enterotoxin C2, in adult ft/ft mice when compared with adult C57BL6 and BALB/c mice, but also when compared with 2‐week‐old ft/ft mice (Fig. a,b) . This indicates an induced expansion of CD4 + T cells expressing TCR Vβ10 in adult ft/ft mice.…”
Section: Resultsmentioning
confidence: 62%
“…It was recently suggested that IL‐17‐mediated skin inflammation in ft/ft mice is driven by infections . S. aureus , a common microorganism found on the skin of patients with AD, produces superantigens that bind to specific TCR β chains . Flow cytometric analysis showed an altered TCR β‐chain repertoire in cells from skin‐draining lymph nodes in ft/ft mice when compared with WT controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since two physicians injected themselves with 3 to 5 g of superantigenic toxin and subsequently developed TSS, it is probable that a very slight infection could induce TSS (37). Several residues of SEC for binding to TCR that are important for superantigenicity have been identified (10,20,22,35). In the present study, we changed N23 of the SEC molecule to A23 and obtained a single-site mutant SEC devoid of superantigenic activity.…”
Section: Discussionmentioning
confidence: 88%
“…and Q210, for binding to TCR are important for superantigenicity (10,20,22,35). In this study, we changed the N23 residue of SEC2 molecule to A23 (Fig.…”
Section: Characteristics Of Msecmentioning
confidence: 99%
See 1 more Smart Citation